Combating corruption in South Africa: assessing the performance of investigating and prosecuting agencies: research - Budhram, Trevor (Acta criminologica, 2018)
Corruption in South Africa is endemic and statistical data show that government is failing to combat this scourge effectively. Mcebisi Jonas, former Deputy Finance Minister, has observed that South Africa has experienced a ‘silent coup’ and become a ‘shadow state’ riddled with corruption, while others say that the country is on the verge of becoming a ‘Mafia state’ and a recipe for a failed state. This article assesses and reports on the performance of role players responsible for the investigation and prosecution of corruption, based on published data from annual reports and statistics for the three-year period 2014/15 to 2016/17. The performance of similar bodies in Hong Kong, Singapore and Lithuania is considered. It is shown that the successes achieved by South African agencies in combating corruption are limited and relatively lower than their three international counterparts.